2023
DOI: 10.1002/adma.202300048
|View full text |Cite
|
Sign up to set email alerts
|

NIR‐II Light Accelerated Prodrug Reduction of Pt(IV)‐Incorporating Pseudo Semiconducting Polymers for Robust Degradation and Maximized Photothermal/Chemo‐Immunotherapy

Abstract: Selective activation of Pt(IV) prodrugs within tumors is particularly attractive because of their low damage to normal tissues. However, current common activation via chemical/photoreduction of Pt(IV) prodrugs into Pt(II) counterparts is limited by undesirable spatial–temporal control over this reduction process and the ineffective tissue penetration depth of undesirable light. Here, a pseudo‐conjugated‐polymer is designed via Stille polymerization, resulting in PSP‐Pt with a Pt(IV) prodrug of oxaliplatin (Oxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Furthermore, the adoption of alternative activation strategies, such as photoactivation or sonosensitization, will be a practical approach to accelerate the reduction process of alkoxido platinum( iv ) complexes and enhance their anticancer efficacy within tumor tissues. 60–66…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the adoption of alternative activation strategies, such as photoactivation or sonosensitization, will be a practical approach to accelerate the reduction process of alkoxido platinum( iv ) complexes and enhance their anticancer efficacy within tumor tissues. 60–66…”
Section: Resultsmentioning
confidence: 99%
“…1 H NMR (400 MHz, CD 3 OD): δ = 3.89−3.86 (t, 2H), 3.13−3.10 (t, 2H) ppm. 13 Preparation of Poly3S. To synthesize Poly3S, a mixture of Mono3S (0.40 mmol, 74.4 mg) and 1,2,4,5-cyclohexanetetracarboxylic dianhydride (0.42 mmol, 94 mg) was dissolved in 5 mL of anhydrous DMF.…”
Section: Methodsmentioning
confidence: 99%
“…Pt­(IV) complexes, commonly exhibiting an octahedral structure, are characterized by their high chemical inertness that results in fewer side effects than Pt­(II) drugs by reducing unfavorable interactions with biomolecules . Upon cellular uptake, inert Pt­(IV) prodrugs can be reduced to highly active Pt­(II) and exhibit cytotoxicity. , In the field of cancer therapy, nanodrug delivery systems have garnered significant attention as they endow small-molecule drugs with tumor-targeting properties due to the enhanced permeability and retention (EPR) effect. , However, the effectiveness of the EPR effect heavily relies on tumor characteristics, necessitating the implementation of more sophisticated drug delivery strategies, such as reduction-responsive polymers, to improve tumor uptake. Considering that the concentration of glutathione (GSH) in tumor cells is significantly higher than that in blood and normal cells, the disulfide bond, which can offer on-demand drug release via fast cleavage in a reducing tumor environment, has been frequently employed in the creation of reduction-responsive polymers. , Recent investigations have revealed that the trisulfide bond, in comparison to the conventional disulfide bond, exhibits improved stability in the presence of low levels of GSH and a blood pool. However, it displays extreme susceptibility to excessive GSH in tumor cells, , thereby demonstrating greater selectivity.…”
mentioning
confidence: 99%
“…37), an oxaliplatin( iv )-based polymer that can be activated by light in the second near-infrared window (NIR-II) (1064 nm) for photothermal and chemo-immunotherapy. 134 NIR-II light has been recognized to be a window of biological transparency and exhibits a much deeper penetration through skin tissues than other wavelengths. 135 What is more, organic photothermal reagents that absorb in the NIR-II region are usually considered to be biosafe and to possess low phototoxicity.…”
Section: Oxaliplatin-based Pt(iv) Prodrugsmentioning
confidence: 99%